Diversionary Behavior for Weak States: A Case Study of Taiwan. (March 2020) - Yeh, Yao-Yuan; Wu, Charles K.S.
This paper explores the mechanisms and circumstances under which leaders in weak states adopt diversionary behavior to deal with domestic problems. We examine the case of Taiwan to see if its President, Tsai Ingwen, has adopted diversionary behavior from 2016 to the present. We found that, unlike great powers, weak-state leaders often resort to non-force tactics such as blaming foreign opponents, but the emergence of diversionary behavior is conditional on the stability of their relationship with a major power. In the case of Taiwan, Tsai adopted a more confrontational foreign policy toward China only when USA–Taiwan relations had become more stable and more favorable toward Taiwan. Future work could continue to explore the circumstances and tools unique to weak states' diversionary behavior.